A Christmas carol - Dickens, Charles, 1812-1870.; Penguin Books (London : Penguin Books, 2009)
A miser learns the true meaning of Christmas when three ghostly visitors review his past and foretell his future.
Young Adult
Keywords: Ilness -- Fiction; Misers -- Juvenile fiction; Poor families -- Juvenile fiction; Scrooge, Ebenezer (Fictitious character) -- Juvenile fiction; Christmas -- Fiction; Ilness -- Fiction; Misers -- Fiction; Poor families -- Fiction; Scrooge, Ebenezer (Fictitious character) -- Fiction; Poor -- Fiction; Scrooge, Ebenezer (Fictional character) -- Fiction; London (England) -- Juvenile fiction; London (England) -- Fiction